2011
DOI: 10.1038/jid.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity Mapping and Whole-Exome Sequencing to Detect SLC45A2 and G6PC3 Mutations in a Single Patient with Oculocutaneous Albinism and Neutropenia

Abstract: We evaluated a 32 year-old woman whose oculocutaneous albinism, bleeding diathesis, neutropenia, and history of recurrent infections prompted consideration of the diagnosis of Hermansky-Pudlak syndrome type 2 (HPS-2). This was ruled out due to the presence of platelet delta granules and absence of AP3B1 mutations. Since parental consanguinity suggested an autosomal recessive mode of inheritance, we employed homozygosity mapping, followed by whole exome sequencing, to identify two candidate disease-causing gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 38 publications
1
55
0
2
Order By: Relevance
“…42 Genomic DNA was extracted from AMS-3.1, -6.1, -7.1 (hyperpigmented, affected), and -7.2 and from BSS-4.2 and -6.1 dermal fibroblasts as well as ATCC adult control, AMS-7.1 (hypopigmented, unaffected), and the mother of AMS-7.2 dermal fibroblasts as unaffected control.…”
Section: Fibroblast Culturementioning
confidence: 99%
“…42 Genomic DNA was extracted from AMS-3.1, -6.1, -7.1 (hyperpigmented, affected), and -7.2 and from BSS-4.2 and -6.1 dermal fibroblasts as well as ATCC adult control, AMS-7.1 (hypopigmented, unaffected), and the mother of AMS-7.2 dermal fibroblasts as unaffected control.…”
Section: Fibroblast Culturementioning
confidence: 99%
“…7 MATP is thought to be important for the proper processing and trafficking of melanosomal proteins Tyr, Tyrp1, Dct (Tyrp2), and seems to act as a proton-dependent transporter at the melanosomal membrane, showing a possible relationship with the P protein (OCA2). 21,22 Moreover, recent data based on experiments of heterologous expression of MATP in Saccharomyces cerevisiae suggested that it also acts as a sucrose transporter. 23 OCA4 clinical phenotype is characterized by a high degree of heterogeneity, ranging from profound hypopigmentation (similar to OCA1A) to near normal skin colour.…”
Section: Introductionmentioning
confidence: 98%
“…Cullinane and colleagues studied a woman with oculocutaneous albinism, recurrent infections, bleeding diathesis, and neutropenia with the working clinical diagnosis of HermanskyPudlak syndrome. 23 However, homozygosity mapping and exome sequencing identified mutations in 2 disease loci: the SLC45A2 gene locus associated with oculocutaneous albinism and the G6PC3 gene locus associated with congenital neutropenia. 23 Additional findings of this woman and her sibling were described by Fernandez and coworkers.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…23 However, homozygosity mapping and exome sequencing identified mutations in 2 disease loci: the SLC45A2 gene locus associated with oculocutaneous albinism and the G6PC3 gene locus associated with congenital neutropenia. 23 Additional findings of this woman and her sibling were described by Fernandez and coworkers. 24 Extending disease phenotype-genotype relationships and disease gene discovery…”
Section: Disease Diagnosismentioning
confidence: 99%